Hygienic assessment and ways to optimize water use for rural and urban population in the Republic of Uzbekistan - Saidova Sokhibakhon Abrorjon kizi; Kodirova Mukhabbat Matkarim hizi (Central Asian Journal of Theoretical and Applied Science, 2022)
The most accessible source of water is now considered to be a centralized water supply system. It is used in the preparation of hot food, drinks, and for drinking raw. The high quality of drinking water is the result of an integrated solution, the main of which are the development and implementation of modern water treatment technologies, the use of social and hygienic monitoring, an integral approach to assessing the quality of drinking water. The high quality of drinking water is the result of an integrated solution, the main of which are the development and implementation of modern water treatment technologies, the use of social and hygienic monitoring, an integral approach to assessing the quality of drinking water.